A Comparison of Percutaneous Kyphoplasty with High-Viscosity and Low-Viscosity Bone Cement for Treatment of Osteoporotic Vertebral Compression Fractures: A Retrospective Study. (9th August 2022) - Wang, Wenhao; Liu, Hao; Wu, Zhikai; Teng, Yun; Huang, Yixue; Liu, Tao; Yang, Huilin
Background: Osteoporotic vertebral compression fracture (OVCF) has become a health issue of worldwide concern. Percutaneous kyphoplasty (PKP) is one of the main surgical methods for OVCFs. This study aimed to evaluate and compare the clinical efficacy and safety of PKP with high- and low-viscosity bone cement for OVCFs. Methods: Totally 62 patients with single-level OVCF were enrolled in this study from December 2018 to April 2021. Among them, 32 cases underwent PKP with high-viscosity bone cement, while 30 cases underwent PKP with low-viscosity bone cement. Visual analog scale (VAS) scores and Oswestry disability index (ODI) scores were used in the pre- and post-operative period to assess patients' rehabilitation. Compression rates of anterior vertebra height (AVH) and posterior vertebra height (PVH) were analyzed to evaluate the restoration of vertebra height. Leakage rates and locations were recorded to show clinical safety. Results: VAS and ODI scores both significantly improved in 2 groups at 1 day, 1 month, and 3 months after surgery. Compression rates of AVH and PVH at 1 day and 3 months after PKP were lower than those before surgery. However, there was no significant difference in VAS scores, ODI scores, and compression rates between both groups. However, PKP with high-viscosity bone cement achieved a lower bone cement leakage rate significantly, which showed the safety of high-viscosity bone cement in PKP. Conclusions: PKP with high- and low-viscosity bone cement both improved the recovery of patients and restored vertebra heights. Notably, PKP with high-viscosity bone cement can achieve favorable clinical outcomes as well as lower bone cement leakage rate.